Piriformospora indica: a root endophytic fungus and its roles in plants - Liu YANG (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2020)
Piriformospora indica is a discovered endophytic fungus colonizing in roots of plants in 1998. The fungus can form the mycelium, mycelial roll, and pear-shaped spores in intercellular and intracellular regions of roots. The fungus colonizes various host plants and also realizes the pure culture in vitro without roots of host plants. P. indica shows many positive effects on host plants, including the promotion of plant growth, the enhancement of nutrient acquisition and stress tolerance, the improvement of disease resistance, and the promoted accumulation of bioactive substances. The commercial production of the fungal spores is established in bioreactor with nanostructured materials “zinc oxide” as nano embedded fungus, which provides provides changes into confers. The review simply summarized the biological characteristics of P. indica, physiological roles in plants, and potential utilization as a biofertilizer.